ChemInform Abstract: Real‐Time and In Situ Monitoring of Mechanochemical Reactions: A New Playground for All Chemists. Issue 49 (December 2015) - Uzarevic, Krunoslav; Halasz, Ivan; Friscic, Tomislav
Abstract: Review: 84 refs.